2004
DOI: 10.1111/j.1365-2427.2004.01242.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the short‐term response of stream diatoms to acidity using inter‐basin transplantations and chemical diffusing substrates

Abstract: 1. Acid-base status has major effects on diatoms, but there is little information on their shortterm response to changing acidity. This is despite the use of diatoms as bioindicators in streams where acid episodes are important during rainstorms (hours to days) or snowmelt (days to weeks). In the Llyn Brianne experimental catchments (Wales, UK), we attempted to mimic the effects of short-term acidification by (i) reciprocally transplanting diatoms between two streams of contrasting acidity and (ii) using acid-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 79 publications
2
40
2
Order By: Relevance
“…typically characterize acidified hill-streams in western Europe while A. minutissimum and Fragilaria spp. are more common at higher pH (Hirst et al, 2002(Hirst et al, , 2004. Similarly, the shift with increasing pH from acidtolerant plecopterans (Amphinemura spp., Leuctra spp., Nemoura spp.)…”
Section: Discussionmentioning
confidence: 95%
“…typically characterize acidified hill-streams in western Europe while A. minutissimum and Fragilaria spp. are more common at higher pH (Hirst et al, 2002(Hirst et al, , 2004. Similarly, the shift with increasing pH from acidtolerant plecopterans (Amphinemura spp., Leuctra spp., Nemoura spp.)…”
Section: Discussionmentioning
confidence: 95%
“…Halvorsen and Heergaard (2007) reported that population sizes of B. rhodani had not fully recovered six months after an AlS treatment. It would, thus, be interesting to know whether slow recolonization rates for Baetis is related to dispersal time alone or if additional factors are involved, such as altered food availability (Hirst et al 2004) or reduced egg survival (Tabak & Gibbs 1991;Yoshimura & Yamada 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Diatoms can respond to changes in water chemistry in a matter of days (e.g. Hirst et al, 2004) and recent work has shown that diatoms exhibit different responses to chronic and episodic acidification (e.g. Passy, 2006).…”
Section: Discussionmentioning
confidence: 99%